Improving Women’s Leadership for Strengthening Health and Nutrition Outcomes in Nagaland, India : Lessons from a Process Evaluation of Community Action for Health and Nutrition - World Bank Group (World Bank, Washington, DC, 2019)
Under the term “communitization,” in 2002 the state government of Nagaland transferred responsibility for local services to Village Councils and sector specific Committees. In the health sector, Village Health Committees were made responsible for management of local health services, including salary payment as well as use of small funds transferred by the state government. Some 1,300 Village Health Committees have been constituted and their level of functionality varies widely, with many hardly active. In 2016, the World Bank-financed NagalandHealth Project included a US 15 million dollar component to provide technical and financial support to strengthen implementation of the communitization strategy. With the objective of improving participation and leadership of women for planning and managing health and nutrition services in the community, the project mandates that all committees appoint a woman Co-chair, in addition to a Chair (who could be a man or woman). The project was initially piloted in 30 villages across two districts, and has been scaled-up in a phased matter since late 2017 to about 450 sites in all 11 districts of the state.